Management of Exercise-Induced Bronchoconstriction - Mark D Inman (Canadian Respiratory Journal)
Exercise-induced bronchoconstriction (EIB) is a common clinical manifestation of asthma, occurring in 70% to 80% of asthmatics. Evidence suggests that exercise and the ensuing bronchoconstriction do not contribute to a worsening of asthmatic inflammation. Asthmatics should not be discouraged from exercising, and, with adequate management, most patients should be able to exercise regularly with only minor symptoms. The first step in the management of patients with EIB should be to obtain optimum control of the underlying asthma, often requiring regular treatment with inhaled steroids. Regular treatment with inhaled corticosteroids usually reduces the extent of EIB by 50% or more. Frequently, despite optimal management of the underlying asthma, patients develop EIB symptoms requiring additional treatment. Short and long acting inhaled beta2-agonists are highly effective at reducing the magnitude of EIB, although there are concerns that the extent of protection diminishes during periods of regular use of these agents. Inhaled cromolyn and nedocromyl are effective at reducing the extent of EIB in some patients, although this protection does not extend beyond 2 to 3 h after treatment. The recently developed leukotriene receptor antagonists are effective at reducing the extent of EIB by 40% to 70%, and have the advantage that this protection lasts throughout the day and does not appear to diminish with regular use. Other agents, including anticholinergics and antihistamines, have been shown to offer partial protection against EIB, suggesting the possibility of using a combination treatment to manage some patients’ symptoms. Finally, there is encouraging evidence suggesting that modifications of the pattern of exercise can markedly reduce the extent of EIB.